(untitled) (Research, Society and Development, 2020)
The present work intends to reflect on the potentiality of Bourdieu’s theoretical-methodological framework for the context of Research in Science Education (RSE) and specifically STS Education, seeking to answer: how the author’s theoretical perspectives have been mobilized/appropriated in the context of RSE? How can this theoretical-methodological framework contribute to the understanding of the emergence of demands/discourses for social participation in ST themes specifically in the context of STS Education? At first, a mapping will be produced, locating the main appropriations in the PEC and highlighting concepts and possibly relevant theoretical investments. To briefly deepen the context of STS Education we conducted a literature review on the CAPES Portal and Google Scholar to advance and update the sources used. The growing presence of the author in this line of research is indicative, although the studies consulted reveal the prevalence of incidental mentions, and the diversity of objects addressed. In the second moment of the research, we will present the theoretical reflection conducted by pointing possibilities of approaches to the concept of social participation and its correlates from the perspectives of the referred author. We support its relevance for understanding the way in which participatory discourses were structured as capitals in this scientific field, as well as for approaches to the current processes of participation themselves, commonly restricted to political-economic-bureaucratic fields, providing the basis for bolder and referenced interpretations in the fields. objective relationships of these processes. For this, it is necessary to establish and/or intensify dialogues with other fields of knowledge, enriching our comprehension capacity and the impact of our practices and proposals.